Optimasi Waktu Pemasakan Bandeng Presto - Suwedo Hadiwiyoto; Sri Naruki (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1999)
A study of the optimation of processing time to produce highly acceptable